Skin and Mucosal Manifestations in NEMO Syndrome: A Case Series and Literature Review. Issue 1 (5th January 2022) - Kohn, Lucinda L.; Braun, Mitchell; Cordoro, Kelly M.; McCalmont, Timothy H.; Shah, Sonal D.; Frieden, Ilona J.; Mathur, Anubhav N.
Abstract: Objectives: To characterize the skin and mucosal findings of NEMO syndrome. Methods: Retrospective review of clinical characteristics from a cohort of two families with mutations in IKBKG (the NEMO‐encoding gene). A literature review identified 86 studies describing 192 patients with IKBKG mutations whose data were also included. Setting: Single center with literature review. Participants: Patients with mutations in IKBKG from our center and reported in the literature. Main Outcomes and Measures: Skin and mucosal characteristics of patients with NEMO syndrome. Results: In addition to ectodermal dysplasia and recurrent infections, male patients had findings of ichthyosis, palmoplantar keratoderma, and inflammatory skin diseases. Both male and female patients had mucocutaneous ulcers and slow‐to‐heal chronic wounds. In combination with patients from the literature, 59% (85/144) of males had ectodermal dysplasia with anhidrosis (EDA) features, and 8% and 10% (12/144; 6/63) of males and females had dental findings, respectively. 4% (6/144) of males and 32% (20/63) of females had mucocutaneous ulcers. Ichthyosis/xerosis was present in 15% of males (21/144) but only 2% (1/63) females. Similarly, 13% (18/144) of male patients presented with dermatitis while this was reported in only 2% (1/63) of females. Conclusions: Our results both confirm and expand upon the known spectrum of mucocutaneous findings in NEMO syndrome. Further genetic studies are needed to correlate specific mutations to clinical and morphologic subtypes.